Artistic and Cultural Afro-Colombian Manifestations. An Approximation to the Case of Girardota (Antioquia, Colombia) - Larraín González, América; Madrid Garcés, Pedro José (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Taking an ethnography developed between 2015 and 2016as a starting point, this article offers a description of theelements that compose the backdrop for the artistic andcultural manifestations of an Afro-descendant community inthe municipality of Girardota, Antioquia.In this way, we conclude that there is an inseparablebond between this community´s participation in political andcommunity organization scenarios, and the ethnical characterattributed to their artistic and cultural manifestations.We priviledge a focus that understands thesemanisfestations as a vehicle for historical, social and politicalreflection. This implies exposing how, after the Constitutionof 1991 and with the implementation of the multiculturaldiscourse in Colombia, population of African descentreformulates its ethnical identity to establish a differentialrelation with regards to its history of slavery and servitude.